Patient Specific Wall Stress Analysis and Mechanical Characterization of Abdominal Aortic Aneurysms Using 4D Ultrasound. Issue 5 (November 2016) - van Disseldorp, E.M.J.; Petterson, N.J.; Rutten, M.C.M.; van de Vosse, F.N.; van Sambeek, M.R.H.M.; Lopata, R.G.P.
Abstract : Objectives: The aim of this study was to perform wall stress analysis (WSA) using 4D ultrasound (US) in 40 patients with an abdominal aortic aneurysm (AAA). The geometries and wall stress results were compared with computed tomography (CT) in seven patients. Additionally, the WSA models were calibrated using 4D motion estimation, resulting in patient specific material parameters that were compared among patients. Methods: 4D-US images were acquired for 40 patients (AAA diameter 27–52 mm). Patient specific AAA geometries and wall motion were extracted from the 4D-US. WSA was performed and corresponding patient specific material properties were derived. For seven patients, CT data were available and analyzed for geometry and wall stress comparison. Results: The 4D-US based 99th percentile wall stress ranged from 198 to 390 kPa. Regression analysis showed no significant relation between wall stress and diameter of the AAA. The similarity indices between US and CT were very good and ranged between 0.90 and 0.96, and the 25th, 50th, 75th, and 95th percentile wall stresses of the US and CT data were in agreement. The characterized patient specific shear modulus had a median of 1.1 MPa (interquartile range, 0.7–1.4 MPa). Based on the maximum AAA diameter, the AAAs were divided in a small, medium, and large diameter groups. The largest AAAs revealed an increased wall stiffness compared with the smallest AAAs. Conclusions: 4D ultrasound is applicable for wall stress analysis of AAAs, and offers the opportunity to perform wall stress analysis over time, also for AAAs who do not qualify for a CT or magnetic resonance imaging. Moreover, the patient specific material properties can be determined, which could possibly improve risk assessment.